A novel modelling and simulation method of hip joint surface contact stress. Issue 1 (2nd January 2017) - Wang, Monan; Wang, Lei; Li, Pengcheng; Fu, Yili
ABSTRACT: Understanding the hip joint surface contact stress distribution characteristics is helpful to determine hip joint biomechanical features and abnormal pathological behavior. Firstly, a 3-dimensional static hip joint biomechanical model is built using analytical method of model in order to study biomechanical properties including bearing area, stress distribution and the peak value of the contact stress of the femoral head, which reveals the relationship between the biomechanical properties and its geometric parameters. Secondly, based on the finite element analysis of the hip joint model, the contact stress distribution on the surface of femoral head is acquired under the condition of the different joint force and the acetabulum coverage rate. Finally, according to the evaluation of the femoral head surface stress and contact stress peak under different load distribution, accuracy and universality of the biomechanical model is verified.